The Tale of Mr Jeremy Fisher - Potter, Beatrix (The Godfrey Cave Group, 1993)
A frog fishing from his lily pad boat doesn't catch any fish, but one catches him.
Keywords: Frogs & Toads; Animals; Juvenile Fiction